Perbaikan Ulang Tata Letak IKM CV Cahaya Tekhnik Abadi Jasa Permesinan - Azizi, Aditya Faisal; Fitra, Fitra; Wicaksono, Dicky Catur; Agel, Rahmat (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
CV Cahaya Tekhnik Abadi is a small and medium enterprise (SMEs) in Dumai thatoperates in the machining services sector, specifically in lathe workshops. Thecompany faces challenges in its production process, such as irregular workflows,material buildup in the work area, and long wait times between processes. This isbecause the current facility layout does not meet operational needs. To address theseissues, two methods were used: Systematic Layout Planning (SLP) and the Graphicalmethod, to redesign a more efficient layout. The analysis showed that the SLP-basedlayout resulted in the shortest material and worker movement distance, at 52.3 meters,compared to 113 meters with the Graphical method. Furthermore, the SLP layoutrequired 25.62 m² of production area, demonstrating better space efficiency. Byimplementing the SLP layout, CV Cahaya Tekhnik Abadi can eliminate unnecessarymovement, streamline workflows, reduce wait times, and lower labor costs. This willincrease productivity while meeting increasing customer demands for quality andspeed of production. Therefore, companies should implement layouts based on theSLP method to significantly improve production performance. Keywords: Graphical Method, Layout, Systematic Layout Planning.